Primary Adrenal Leiomyosarcoma in an Arab Male: A Rare Case Report with Immunohistochemistry Study - Veena Nagaraj; Mohammed Mustafa; Essa Amin; Waleed Ali; Shamil Naji Sarsam; Abdulla Darwish (Case Reports in Surgery)
Primary adrenal leiomyosarcoma is a rare form of adrenal mesenchymal tumors. Immunohistochemistry (IHC) together with histology takes a major role in determining the tumor type and predicting their biological behavior and differentiating them from adrenal cortical carcinoma. Appropriate radiological investigation is necessary to rule out metastatic disease from primary tumors elsewhere in the body. In this case, we report a primary leiomyosarcoma of the adrenal gland in a 61-year-old Bahraini male clinically presumed to be a renal neoplasm.